Administrative Penalty as an Instrument of Restriction of Freedom of Enterprise and Rights of Ownership: a Point of View - Grechkina, Olga V. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article considers different points of view of scientists, the judiciary, executive bodies containing critical changes in the legislation on administrative offences in the direction of strengthening administrative responsibility for the offense. The Author comes to the conclusion that the introduction of the Code of Administrative Offences of the Russian Federation changes should be aimed at the elimination of excessive restrictions of economic freedom and property rights of legal entities while being brought to administrative responsibility.